TINJAUAN HUKUM ISLAM TERHADAP PENGGUNAAN E-WALLET SEBAGAI SISTEM PEMBAYARAN BERBASIS ELEKTRONIK DI KALANGAN MAHASISWA - Irsan Taufik; Muhammad Anis; Ashar Sinilele (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2023)
Abstract The development of E-wallet grows in tandem with the emergence of E-commerce and Marketplaces. Payment instruments for products/services that consumers want to buy can be done anywhere and anytime using their smartphone with top up on E-wallet. The key to the success of the two technology products above is the ease of transactions and the top-up system. Based on BI regulations, E-wallet is an electronic service for storing data and other payment instruments using cards and electronic money that accommodates funds that can be used for transactions. Islam views E-wallet as a treasure (tsaman) by the community, whether it consists of metal, printed paper or from any material, then issued by an authorized financial institution. However, E-wallet also has a gharar nature in that contracts that occur between companies are not clear and do not follow sharia principles so that the rights and obligations of the parties are unclear. E-wallet as a payment method that appeared later, basically if we search in the Qur'an and hadith, we will find it difficult to find the arguments that specifically regulate it. The possibility of Gharar elements in the use of E-wallet attracts researchers to raise issues related to the use of E-wallet among students of the Sharia Economics Law Study Program, Uin Alauddin Makassar. Keywords: Islamic law, use of E-wallet, electronic-based payments